Correlation between antibutyrylcholinesterasic and antioxidant activities of three aqueous extracts from Tunisian Rhus pentaphyllum - Delai Afef; Houas Ikram; Mbarek Sihem; Yatouji Sonia; Mansour Hedi; Dridi Dorra (BMC, 2011)
Abstract For centuries, plants have been used in traditional medicines and there has been recent interest in the chemopreventive properties of compounds derived from plants. In the present study, we investigated the antibutyrylcholinestrasic (anti-BuChE) and antioxidant (against some free radicals) activities of extracts from Rhus pentaphyllum. Aqueous extracts were prepared from powdered R. pentaphyllum roots, leaves and seeds and characterized for the presence of tannins, flavonoids and coumarins. Seeds aqueous extract contained the highest quantities of both flavonoids and tannins (21.12% and 17.45% respectively). In the same way, seeds extracts displayed remarkable inhibition against BuChE over 95%, at 100 μg/ml and with IC50 0.74 μg/ml. In addition, compared to leaves and roots extracts, seeds aqueous extract revealed relatively strong antiradical activity towards the ABTS.+ (IC50 = 0.25 μg/ml) and DPPH (IC50 = 2.71 μg/ml) free radicals and decreased significantly the reactive oxygen species such O2.- (IC50 = 2.9 μg/ml) formation evaluated by the non-enzymatic generating O2.- system (Nitroblue tetrazolium/riboflavine). These data suggest that the anti-BuChE activities mechanism of these extracts occurs through a free radical scavenging capacities. The present study indicates that extracts of Rhus pentaphyllum leaves, seeds and roots are a significant source of compounds, such as tannins, flavonoids and coumarins, with anti-BuChE and antioxidant activities, and thus may be useful for chemoprevention.